Fenomena Dorongan Menikah: Penyelesaian Konflik Orang Tua dengan Anak melalui Komunikasi Antarpribadi - Pertiwi, Esa; Kusumajanti, Kusumajanti; Sutowo, Irpan Ripa’I (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2021)
Encouragement from parents to get their children to get married often creates conflicts. This study analyzes interpersonal communication which is used as an effort to resolve conflicts. Qualitative methods are used to answer research questions with a phenomenological approach. The results obtained by parents often encourage their children who are old enough to get married. Conflicts between parents and children often occur when the child doesn’t feel like getting married, while the parents for several reasons want their child to get married soon. The interpersonal communication built by parents and children can be a way to resolve conflicts that occur. Openness and listening are the keys to the communication process between parents and children. This study concludes that the conflict between parents and children regarding the urge to marry must be resolved using interpersonal communication.